No evident association of nasal carriage of Staphylococcus aureus or its small-colony variants with cotrimoxazole use or ANCA-associated vasculitis relapses. (24th June 2019) - Tan, Boun Kim; Crabol, Yoann; Tasse, Jason; Laurent, Frédéric; Nekkab, Narimane; Vinter, Christine; Puéchal, Xavier; Guillevin, Loïc
Abstract: Objective: To identify the role of Staphylococcus aureus (SA) or its intracellular small-colony variant phenotype (SCV) with co-trimoxazole (CTX) or ANCA-associated vasculitis (AAV) activity. Methods: All consecutive AAV patients with granulomatosis with polyangiitis (GPA), eosinophilic GPA or microscopic polyangiitis, followed at the French National Vasculitis Referral Center (09/2012–05/2013), and hospitalized non-AAV controls, exclusively for SA/SCV carriage comparisons, were enrolled. All had bilateral anterior nasal swab cultures. Nasal SA or SCV carriage was determined and associations with relapse(s), BVAS, ANCA-positivity, anti-staphylococcal and immunosuppressant use, were analysed ⩾4 years post-inclusion. Results: Nasal SA carriage rates did not differ among AAVs ( P = 0.53): GPA (24/80; 30%), EGPA (7/28; 25%) and microscopic polyangiitis (3/11; 27.3%); and the rate was less frequent in controls than in GPA patients not taking CTX ( P = 0.04). AAV patients taking CTX prophylaxis had less nasal SA carriage (8.7% vs 36.2%; P = 0.02). Nasal SA carriage or CTX use did not modify relapse rates, BVAS or ANCA-positivity at inclusion or during follow-up. Nasal SCV carriage, found in 15/207 (7.2%) patients, was similar for GPA (10/24; 41.7%), microscopic polyangiitis (2/7; 28.6%) and eosinophilic GPA (2/3; 66.7%), but higher ( P = 0.02) than controls (1/14; 7.1%). SCV carriage by AAV groups did not modify relapse rates or ANCA positivity at inclusion or during follow-up; a trend towards higher BVAS was observed only for anti-PR3 ANCA patients. Conclusion: Nasal SA or SCV carriage was comparable among AAVs but more frequent than in controls. Nasal SA or SCV carriage and CTX use did not modify AAV relapse rates.